Geographical distribution of tomato crop marketing centers in the governorates of Basra and Dhi Qar for the agricultural season (2018-2019) - Khazal Moazi , Assist. Lect. Hassna; Ramadan Mohammed, Prof. Dr. Mohammed (Basra studies journal, 2022)
It was found that the total number of marketing centers for fruits and vegetables in the governorates of Basra and Dhi Qar amounted to (13) marketing centers distributed over (12) administrative units representing (36.1%) of the total administrative units amounting to (36) administrative units and this is represented by (5) marketing centers in the governorate Basra is distributed over the districts of (Al-Madina, Qurna, Al-Dair, Basra, and Al-Zubayr), and (8) marketing centers in Dhi Qar governorate, with two marketing centers in Nasiriyah district and the rest in the districts of Al-Rifai, Suq Al-Shuyoukh, Al-Nasr, Al-Shatra, Al-Gharraf and Qalaat Sukkar. %) of the total marketed quantities of the tomato crop, which are the tomato marketing center in Zubair district and the (new) fruit and vegetable marketing center in Nasiriyah district, while the number of marketing centers to which it is marketed is less than (14.7%) of the total marketed quantities of tomato crop ( 11) A marketing center.